MENGUCAPKAN SELAMAT NATAL DAN SELAMAT HARI RAYA PADA AGAMA LAIN: Studi al-Quran dan al-Hadits Multikultural - Moh Afiful Khair; Jamiliya Susantin; Syamsul Rijal; Moh Soheh (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2023)
The pros and cons of saying "Merry Christmas and Happy Holidays of other religions" conveyed by the ulema have their own basic arguments. The legal status of saying Congratulations has its own charm for researchers so researchers raise this theme. The research method used by library research researchers with the conceptual approach used. This study seeks to describe the behavior of the Muslim community who congratulate them from the perspective of the Koran and al-Hadith. The collection of data in this study is through the study of documents which are checked by reading, analyzed, then connected with interpretation and presented descriptively. The results of this study indicate that scholars and intellectual figures are allowed to wish Merry Christmas and Happy Holidays to other religions by setting arbitrary boundaries instead of acknowledging their theology, Qardhawi also explained that there is nothing that prevents congratulating on non- Muslims, however, do not participate in commemorating their religious rituals, nor do they celebrate. We may live with them (non-Muslims) by doing something that is not contrary to Allah's law. The implication is that the life of this multicultural society can be intertwined with love and the creation of peace in the midst of society.